In situ study of the film formation mechanism of organic–inorganic hybrid perovskite solar cells: controlling the solvate phase using an additive system. Issue 16 (1st April 2020) - Lee, Sehyun; Tang, Ming-Chung; Munir, Rahim; Barrit, Dounya; Kim, Yeon-Ju; Kang, Rira; Yun, Jin-Mun; Smilgies, Detlef-M.; Amassian, Aram; Kim, Dong-Yu
Abstract : The role of the additive and solvate phases in the direct formation of perovskite crystals was revealed by in situ analysis during spin-coating condition. Abstract : As a coating method compatible with printing, one-step spin-coating is widely used for fabricating perovskite thin films. Controlling the crystal growth rate of two precursors is essential to obtain a homogeneous film morphology. However, the film formation mechanism and role of solvate systems during spin-coating have not yet been clearly revealed. In this work, we implemented the in situ grazing incidence wide-angle X-ray scattering of CH3 NH3 PbI3 perovskite material based on various additive systems to adjust the unbalanced crystal growth rate of CH3 NH3 I and PbI2 . As we expected, the behavior of the solvate phase was strikingly mediated by various additives, and one of the additives greatly slowed the PbI2 solvate phase, thus overcoming the imbalance in the crystal growth rate. Consequently, the well-controlled perovskite films have both good film morphology and high photovoltaic performance with excellent reproducibility.